The Effect of Total or Partial Protected Vegetable Oil Supplementation on In Vitro Digestibility, Feed Fermentability and Energy Efficiency - Laily Ismatul Faizah; Widiyanto Widiyanto; Anis Muktiani (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study was examines the effect of oil (oil palm and corn) combination with the level of protection (total or partial) on feed fermentability, methane production and energy efficiency with in vitro techniques. The experiment was designed using a factorial pattern 2x2, factor A = type of oil (corn and palm) and factor B = oil protection level (total and partial), each treatment combination was repeated 4 times. Data was processed by analyzing various factorial patterns in a randomized block design and if there was an influence between treatments performed by the Dunca test. The results showed that there was no interaction effect (P>0.05) between the types of oil with the level of protection in all parameters, except NH3. Supplementation of palm oil produces total volatyle fatty acids (VFA), acetate and methane (CH4) production higher than corn oil (P<0.05), but the efficiency of converting hexose energy to VFA (ECH) was lower (P<0.05) (76.09 vs 77.80%). Supplementation of total protected oil decreased in the protozoa population, resulting in higher dry matter digestibility (DMD) and organic matter digestibility (OMD), but lower ECH yield compared to partial protected oil supplementation (P<0.05), ie 76.68 vs 77.22%. The conclusions of the study are corn oil produce of ECH higher than palm oil. Partial protection produce better feed fermentability and increasing energy efficiency in the form of decreasing A/P ratio and methane production.